THE EFFECT OF USING ATLAS TEACHING AIDS ON STUDENTS LEARNING INTEREST IN SOCIAL STUDIES (IPS) LESSON IN GRADE 5 AT MADRASAH IBTIDAIYAH MIFTAH ASSA’ADAH, SOUTH TANGERANG, BANTEN - Putri, Lutfia Anita; Muhtadi, Mohammad; Munawaroh, Laila (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to determine the effect of using atlas teaching aids on students’ learning interest in Social Studies (IPS) subject in Grade V at MI Miftah Assa’adah, South Tangerang. The research method used is an experimental method with a Nonequivalent Control Group Design. The research subjects consisted of two classes: a control class that used conventional teaching methods, and an experimental class that used atlas teaching aids during the learning process. The results of the study showed that the control class obtained an average final score of 52.13, while the experimental class obtained an average final score of 59.04. An independent t-test on the post-test data showed a significance value (2-tailed) of 0.001 < 0.005, which means there is a significant difference in students’ learning interest between those who used atlas teaching aids and those who were taught using conventional methods. Therefore, it can be concluded that the use of atlas teaching aids has a positive and significant effect on increasing students’ learning interest in the Social Studies subject in Grade V at MI Miftah Assa’adah, South Tangerang.